«ШӘРИЯР» ДӘСТАНЫНДА БИЛИМЛЕНДИРИЎ МӘСЕЛЕЛЕРИ - Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2020)
The article deals with issues of education in the epos «Shariyar» suitable age of giving children to school, duration of study, importance of science and knowledge in the life of a percon and society, using computer technologies in the study process.
Keywords: folklore work; knowledge; school; study; continuation of study; computer technology; imagination; talisman; tutor; voral; immoral; riddle; cognoscenti